Juridical Review of Imposition of Deeds for Granting of Collective Rights in Sharia Banking in Indonesia - Syifa Esthiningtyas Putri Widodo; Benny Djaja (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
This study aims to describe and then find out how the granting of Mortgage Deeds institution Sharia Banking Finance made by Land Deed Officials regulated in the Regulation of the Head of the National Land Agency Number 8 of 2012 concerning Amendments to the Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 concerning Provisions for Implementation of Government Regulation Number 24 of 1997 concerning Registration Land As well as affiliated provisions. By using the Normative Juridical research method with the conclusions: 1. The granting of Mortgage Guarantees for financing contracts in Islamic banking is guided by the Mortgage Law which proves the occurrence of a mixture of two principles in the implementation of mortgage guarantees in Indonesia; 2. Formulation of the Mortgage Deed Institution Islamic Banking Finance uses the same formulation as Conventional Banking Financial Institutions, so it needs to be designed separately for the Formulation of the Deed of Imposing Sharia Mortgage on several Sharia terminologies.